Haemophilia care in Iraq; a multi-centre study - Nidal Karim Al Rahal; Meaad Kadhum Hassan; Obeida Amir Abid; Azeezah Mohammed Mohsin (Journal of the Pakistan Medical Association, 2024)
Objectives: To evaluate the level of care available to haemophilia patients. Method: The descriptive, retrospective analytical study was conducted from December 15, 2020, to March 1, 2021, after approval from the Mustansiriyah University, Baghdad, Iraq, and comprised data from 3 haemophilia treating centres in Iraq participating in the World Bleeding Disorders Registry. The data collected related to patients with haemophilia A and B enrolled in the registry since March 2018, and included age at diagnosis, type of haemophilia, disease severity, age at first bleed and at first joint bleed, type of replacement therapy and outcome. Data was analysed using statistical package of social sciences (SPSS) version 20. Results: Of the 638 patients with mean age 16.2±4.3 (range: 9-29 years), 581(91%) had haemophilia A, 57(8.9%) had haemophilia B, 385(60.5%) had severe haemophilia, 126(19.8%) moderate and 125(19.7%) mild. Further, 259(41%) patients had been diagnosed for <1 year. There were 1354 bleeding events, and hemarthrosis accounted for 959(70.8%) of them. The mean annualised bleeding rate for severe patients was 2 ± 0.6(range 0-4), while the mean annualised joint bleeding rate was 4 ± 1.3(range :2-8). There were 256(32.3%) patients who were tested for inhibitors, and 62(24.3%) were positive. Among 426(73.3%) haemophilia A patients with a treatment history, 248(58%) were on prophylactic therapy, and the corresponding value among 37(65%) haemophilia B patients was 17(46%). Conclusions: access to treatment was found to be limited, and patients were found to be suffering from high bleeding rates and joint damage. Key Words: Haemophilia A and B, Hemarthrosis, Health Services, Acuity